(untitled) (Politeja, 2020)
The Evolution of the Concept of Hans-Dietrich Genscher in the German Détente Policy in the Years 1974-1989. Genesis – Instruments – Impact The main aim of this article is to present the genesis, instruments and real influence of the concept of the “realistic” détente policy of the German Minister of Foreign Affairs Hans-Dietrich Genscher on the foreign policy of the German federal government in the years 1974-1989. The author formulates a thesis that Genscher’s concept had very significant influence on the program activities of the FDP as well as on the practical foreign policy of the SPD/FDP governments (1974-1982) and CDU/CSU/FDP governments (1982-1989), whereby the year 1985 was an important turning point in this evolution.